2020
DOI: 10.1177/2055217320960499
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation of multiple sclerosis: Results from the national registry of the disease in Saudi Arabia

Abstract: Background Multiple Sclerosis (MS) is a chronic CNS inflammatory disease commonly affecting young adults. Both genetics and environmental factors have been reported to have a role in pathophysiology of the disease. Objective This article aims to report familial nature and aspects of MS in Saudi Arabia. Method The study utilized data collected by the National Saudi MS Registry between 2015 and 2018; especially data relevant to the familial history of MS. SPSS 22 was used for all analysis and reporting. Statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 32 publications
0
13
2
Order By: Relevance
“…6 , in each study, the first number is the number of FMS cases and the second number is the number of FMS plus sporadic cases (both in that particular gender). For instance, in the study of AlJumah et al, 107 men and 208 women with FMS and 710 men and 1440 women with sporadic MS were recruited [ 16 ]; therefore, the rate of FMS in men and women was calculated to be 107/817 (710 + 107) and 208/1648 (208 + 1440), respectively. The OR of male/female in FMS cases was not statistically significant (OR = 0.9; 95% CI: 0.6–1.2, P = 0.55) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 , in each study, the first number is the number of FMS cases and the second number is the number of FMS plus sporadic cases (both in that particular gender). For instance, in the study of AlJumah et al, 107 men and 208 women with FMS and 710 men and 1440 women with sporadic MS were recruited [ 16 ]; therefore, the rate of FMS in men and women was calculated to be 107/817 (710 + 107) and 208/1648 (208 + 1440), respectively. The OR of male/female in FMS cases was not statistically significant (OR = 0.9; 95% CI: 0.6–1.2, P = 0.55) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, cohort studies could be well suited on the account of a longer time period for the accumulation of new cases in the family. Concerning the degree of relatedness, the occurrence of the same condition is more prevalent in rst-degree relatives, particularly siblings of the affected individuals, which underscores the combined role of shared genetic and environmental factors in MS etiology [16,24,25,29,33,34]. While, one study reported parent-child relationship as the prevalent kinship [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it seems that the worldwide frequency of FMS is steady-state over time. Nonetheless, some studies in middle-east reported the increasing [13,24] or decreasing [16] prevalence of FMS over time, highlighting the existence of substantial difference in terms of genetic and environmental factors between different populations even in a same geographical area. Moreover, the overwhelming majority of the studies have been performed in a cross-sectional setting; while, su cient long follow-up period is needed to evaluate the development of the disease in new members of the relatives, primarily distant relatives that would not have been found in short-term periods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations